Pregunta
upstudy study bank question image url

Solve the formula for the given variable. \[ Z=\frac{9}{f-s} \] Solve for \( f \), then solve for \( s \). \( f=\square \) (Simplify your answer.)

Ask by Marshall Reed. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\( f = \frac{9 + Zs}{Z} \) and \( s = \frac{-9 + Zf}{Z} \).

Solución

Solve the equation \( Z=\frac{9}{f-s} \). Solve the equation by following steps: - step0: Solve for \(f\): \(Z=\frac{9}{f-s}\) - step1: Swap the sides: \(\frac{9}{f-s}=Z\) - step2: Cross multiply: \(9=\left(f-s\right)Z\) - step3: Simplify the equation: \(9=Z\left(f-s\right)\) - step4: Swap the sides: \(Z\left(f-s\right)=9\) - step5: Divide both sides: \(\frac{Z\left(f-s\right)}{Z}=\frac{9}{Z}\) - step6: Divide the numbers: \(f-s=\frac{9}{Z}\) - step7: Move the constant to the right side: \(f=\frac{9}{Z}+s\) - step8: Add the terms: \(f=\frac{9+sZ}{Z}\) - step9: Simplify: \(f=\frac{9+Zs}{Z}\) Solve the equation \( Z=\frac{9}{f-s} \). Solve the equation by following steps: - step0: Solve for \(s\): \(Z=\frac{9}{f-s}\) - step1: Swap the sides: \(\frac{9}{f-s}=Z\) - step2: Cross multiply: \(9=\left(f-s\right)Z\) - step3: Simplify the equation: \(9=Z\left(f-s\right)\) - step4: Swap the sides: \(Z\left(f-s\right)=9\) - step5: Divide both sides: \(\frac{Z\left(f-s\right)}{Z}=\frac{9}{Z}\) - step6: Divide the numbers: \(f-s=\frac{9}{Z}\) - step7: Move the constant to the right side: \(-s=\frac{9}{Z}-f\) - step8: Subtract the terms: \(-s=\frac{9-fZ}{Z}\) - step9: Change the signs: \(s=\frac{-9+fZ}{Z}\) - step10: Simplify: \(s=\frac{-9+Zf}{Z}\) The solution for \( f \) is \( f=\frac{9+Zs}{Z} \) and the solution for \( s \) is \( s=\frac{-9+Zf}{Z} \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve for \( f \), we start with the equation \( Z=\frac{9}{f-s} \). First, we multiply both sides by \( (f-s) \) to eliminate the fraction: \[ Z(f-s) = 9. \] Now, we can distribute \( Z \): \[ Zf - Zs = 9. \] Next, we want to isolate \( f \): \[ Zf = 9 + Zs. \] Now, dividing by \( Z \): \[ f = \frac{9 + Zs}{Z}. \] Now, to solve for \( s \), we start again from the original formula: \[ Z=\frac{9}{f-s}. \] Multiplying both sides by \( (f-s) \): \[ Z(f-s) = 9. \] Distributing again gives: \[ Zf - Zs = 9. \] Rearranging to isolate \( s \): \[ Zs = Zf - 9. \] Now we divide by \( Z \): \[ s = \frac{Zf - 9}{Z}. \] Thus, we have the solutions as follows: \( f=\frac{9 + Zs}{Z} \) and \( s=\frac{Zf - 9}{Z}. \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad